Mutation analysis of the MYH gene in unrelated Czech APC mutation-negative polyposis patients - Sulová, M; Zídková, K; Kleibl, Z; Stekrová, J; Kebrdlová, V; Bortlík, M; Lukás, M; Kohoutová, M (European journal of cancer (Oxford, England, 2007)
Some of the APC negative FAP and AFAP cases have recently been found to be attributable to MYH associated polyposis (MAP). MAP is an autosomal recessive syndrome associated with 5-100 colorectal adenomas and caused by mutation in the MYH gene. Here, we screened for germline MYH mutations in 82 APC-mutation-negative probands with classical and attenuated familial adenomatous polyposis using the denaturing high performance liquid chromatography (DHPLC) method in combination with sequencing. Altogether 12 previously reported changes and four novel genetic alterations, mostly in intronic sequences, were identified. The results revealed the presence of biallelic germline MYH mutations in two patients. These patients were compound heterozygotes for two of the most common germline mutations c.494 A>G (p.Y165C); c.1,145 G>A (p.G382D). These variants are established to be associated with adenomatous polyposis and colorectal cancer. No novel pathogenic mutation has been identified in our study.
Keywords: familiární adenomatózní polypóza; geny APC; zárodečné mutace; DNA Mutational Analysis; exony; Myosin Heavy Chains; Exons; Germ-Line Mutation; Česká republika; DNA nádorová; Humans; lidé; Czech Republic; Genes, APC; DNA, Neoplasm; těžké řetězce myosinu; Adenomatous Polyposis Coli; mutační analýza DNA